Tanshinone IIA attenuates AOM/DSS-induced colorectal tumorigenesis in mice via inhibition of intestinal inflammation - Lijie Liu; Hanjing Gao; Tao Wen; Tao Gu; Shuang Zhang; Zhiyong Yuan (Taylor & Francis Group, 2021)
Context Tanshinone IIA is a natural extract derived from a Chinese medicinal herb with multiple bioactivities; however, whether and how tanshinone IIA protects against colorectal cancer (CRC) are uncertain. Objective We investigated the potential beneficial effects of tanshinone IIA in a colitis-associated colorectal tumorigenesis mouse model and its underlying mechanisms. Materials and methods Male C57BL/6 mice were treated with azoxymethane (AOM) 10 mg/kg body weight and dextran sulphate sodium (2.5% DSS) to induce a colitis-associated cancer model. Tanshinone IIA (200 mg/kg body weight) was given to the mice intraperitoneally. After 12 weeks, all mice were sacrificed to measure tumour formation, intestinal permeability, neutrophil infiltration, and colonic inflammation. In addition, whether tanshinone IIA has inhibitory effects on neutrophil activation was determined through in vitro investigations. Results We observed that tanshinone IIA significantly decreased tumour formation in AOM/DSS-treated mice compared to AOM/DSS-treated alone mice (0.266 ± 0.057 vs. 0.78 ± 0.153, p = 0.013). Tanshinone IIA also decreased intestinal permeability compared to that in AOM/DSS-treated alone mice (3.12 ± 0.369 vs. 5.06 ± 0.597, p = 0.034) and consequently reduced neutrophil infiltration of the colonic mucosa (53.25 ± 8.85 vs. 107.6 ± 13.09, p = 0.014) as well as intestinal inflammation in mice. Mechanistically, tanshinone IIA downregulated the NF-κB signalling pathway in the colonic tumours of AOM/DSS-treated mice. In vitro assays further validated that tanshinone IIA suppressed LPS-induced neutrophil activation. Conclusion These data suggest that tanshinone IIA alleviates colorectal tumorigenesis through inhibition of intestinal inflammation. Tanshinone IIA may have a therapeutic potential for CRC in clinical practice.